ANALISIS KELENGKAPAN APLIKASI DAN PELAYANAN TERHADAP KEUNGGULAN BERSAING GO-JEK - Khumairoh, An Nisa; Andayani, Sri; Novaria, Rachmawati (Universitas 17 Agustus 1945 Surabaya, 2018)
The rapid technological advancement of all aspects of the field has created many new business opportunities,one of which is modern transportation business using with internet. GOJEK as ameans of online transportation that much in demand by the community because it felt to provide many benefits. With the positive progress and positive feedback from the community, many emerging similar transportation that uses the internet as its supporters Of the many online transport services GO-JEK. Offers a wide range of applications Offering services as well as providing GO-JEK as a superior online transportation compared toothers.Â Keywords:.Completeness.of.Application,.Service,.Competitive.Advantage.